Population Growth and Resource Degradation: The Case of Water in the Indigenous Territories Boruca and Térraba from the Pacific of Costa Rica (2000-2019) - Bartels Villanueva, Jorge (2021)
This article investigates the social management of water resources in the indigenous communities Ojo de Agua and Crun Shurin, from the Pacific of Costa Rica, with the intention of identifying the social and institutional actors involved, as well as the relationships between them. Specifically, the challenges in access to water manifested by indigenous people from both communities are explored, as well as the role of state institutions in the search for solutions to these problems. Group interviews, statistics on population growth in the two territories were used and the quality of the water consumed daily was evaluated, through laboratory analysis, to identify possible sources of contamination.